Pengembangan Sistem Informasi Manajemen Akademik Sekolah Menengah Atas (Studi Kasus pada SMA Sejahtera 1 Depok) - Ammar Burhanuddin Sayuti; Ahmad Afif Supianto; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Sejahtera 1 Depok Senior High School is one of the educational institutions in Depok city under the auspices of the family sejahtera bandung foundation. Main tasks Sejahtera 1 Senior High School is practice the learning process, evaluate of study result students, and graduate qualified students with the required standards. However, there are several things such as the process of registration new students is still manually, and the process of evaluate students, the distribution of ratings for student report is very complex. Therefore the need for information systems that can help deal with the problem. Development of school academic management information systems using waterfall model. Which is conducted phase is requirement analysis, design, implementation, and testing. After the result of the User Acceptance Test given to the BPTIK teacher as a admin (the percentage of UAT by 90%), the teacher as student assessor (the percentage of UAT by 90%), and prospective student as registrant (the percentage of UAT by 85%).